The mice focusing solenoids and their cooling system - Green, M; Barr, G; Lau, W; Senanayake, R; Yang, S (2005)
This report describes the focusing solenoid for the proposed Muon Ionization Cooling Experiment (MICE) [1]. The focusing solenoid consists of a pair of superconducting solenoids that are on a common bobbin. The two coils, which have separate leads, may be operated in the same polarity or at opposite polarity. This report discusses the superconducting magnet design and the cryostat design for the MICE focusing module. Also discussed is how this superconducting magnet can be. integrated with a pair of small 4.2 K coolers.